Effect of agitation and aeration on bioconversion of domestic wastewater sludge in a batch fermenter - Alam, Md. Zahangir; Fakhru'l-Razi, A. (Informa UK Limited, 2002)
Effects of agitation and aeration rate on microbial treatment of domestic wastewater sludge were investigated in a batch fermenter using mixed culture of Penicillium corylophilum and Aspergillus niger. It was found that liquid state bioconversion (LSB) of wastewater sludge was highly influenced by the effects of agitation and aeration. The maximum production of sludge cake and reduction of organic substances in treated sludge were recorded at 150-200 rpm of agitation speed and 0.5 vvm of aeration rate after 72 h of treatment. No effective results were observed at higher rate of agitation (300 rpm) and aeration (1.5 vvm) as compared to optimum values. The results showed that the minimum level of air saturation (pO2) was adequate to maintain the bioconversion process.